Design, synthesis and insecticidal activities of new meta-diamide compounds containing n-butyl group. (27th April 2022) - Huang, Pengmian; Wu, MingHui; Lv, Liang; Zhou, Liqi; Liu, Xiangwei; Liu, Jiyong
Graphical abstract: 18 new meta-diamide compounds containing n -butyl group were designed, synthesized and evaluated against Plutella xylostella, Spodoptera frugiperda and Alfalfa sprouts for their insecticidal activities. The preliminary bioassay indicated that some of them exhibited favorable insecticidal activities. Abstract: In order to discover a novel insecticide, a series of meta -diamide compounds containing n -butyl group were designed and synthesized. Preliminary bioassay data showed that some of the target compounds exhibited good insecticidal activities against Plutella xylostella, Spodoptera frugiperda and Alfalfa sprouts. In particular, compounds 6d and 6n displayed 100% insecticidal activity against Plutella xylostella at 1 mg/L and also revealed 100% of mortality rate against Spodoptera frugiperda at 0.1 mg/L, which was consistent with the cyproflanilide. Meanwhile, compound 6m showed 98.89% insecticidal activity against Alfalfa sprouts at 100 mg/L, better than cyproflanilide (25.60% at 100 mg/L). The work demonstrated that compounds containing n -butyl group might supply certain hints toward structure optimization design for the development of new insecticides.